2020
DOI: 10.21837/pm.v18i13.776
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholder Management of Conservation in Lower Kinabatangan Sabah

Abstract: Effective conservation measures are essential to protect nature and wildlife which act as flagship attraction for ecotourism to flourish. The study focuses on conservation management of natural forests and wildlife by multiple stakeholders in Lower Kinabatangan Sabah. Rare and endangered wildlife species is the main attraction for ecotourism development in this area. The study employed a mixed method research by integrating quantitative and qualitative approaches. Analyses revealed contradictory findings where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…We employed a qualitative content analysis method known as manifest analysis (Elo and Kyngäs, 2008;Bengtsson, 2016;Carlson, 2018;Okumah et al, 2020;Pimid et al, 2020) to examine interview transcripts. This method emphasizes staying close to the original data and is unique because it has both quantitative and qualitative methodology.…”
Section: Interview Analysesmentioning
confidence: 99%
“…We employed a qualitative content analysis method known as manifest analysis (Elo and Kyngäs, 2008;Bengtsson, 2016;Carlson, 2018;Okumah et al, 2020;Pimid et al, 2020) to examine interview transcripts. This method emphasizes staying close to the original data and is unique because it has both quantitative and qualitative methodology.…”
Section: Interview Analysesmentioning
confidence: 99%
“…However, our interviews revealed that in the case of scientific wildlife results (i.e., population distribution and abundance, habitat availability, and wildlife crimes), they were not shared properly with local indigenous people during conservation awareness programs. If provided with the right conservation message, the community and private sector could become actively involved during the planning, decision making, and evaluation stages, and raise their moral beliefs and values toward pro-conservation behavior [ 52 , 53 , 54 ]. Voicing opinions for conservation practices in line with social-economic needs, and built on local knowledge, would gain traction for supporting conservation [ 18 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, dive tourism and water sports activities have posed threats to the marine ecosystem caused by anchor damage to the seabed and trampling and touching of coral reefs and marine wildlife (Asian Development Bank, 2014). Conserving the protected areas highly depends on effective environmental management by the stakeholders in the respective areas (Pimid et al, 2020). However, ensuring the sustainability of the ecosystem has many challenges.…”
Section: Introductionmentioning
confidence: 99%